Landfill leachate treatment technology via electrocoagulation: a review of operating parameters, intensification, and modelling - Hanif M.H.M.; Kamaruddin M.A.; Norashiddin F.A.; Niza N.M.; Shadi A.M.H.; Sabri M.N.I.M.; Zawawi M.H. (Desalination Publications, 2023)
coagulation; electrokinesis; landfill; leachate; municipal solid waste; oxidation; wastewater treatment